Structural change, environmental pollution and health expenditure: Evidence from a global panel - Dobdinga Cletus Fonchamnyo; Etoh-Anzah P. Angyie; Nges S. Afumbom; Gildas D. Dinga; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
This study examined the effects of structural change and environmental pollution on health expenditure, while controlling for globalization. A panel data from 1995 to 2019 for 115 countries was used, while the estimation of results was done based on the Driscoll-Kraay technique. The estimation was conducted for different income levels as well as sub-regional groupings. The results revealed that two components of structural change, manufacturing valueadded and service value-added significantly increased health expenditure in the world. Economic globalization and financial globalisation were also found to significantly reduce health expenditure while social globalisation, environmental pollution and interpersonal globalisation were found to significantly increase health expenditure in the world. The income level analysis revealed that manufacturing value-added significantly increased health expenditure in lowmiddle-income and upper-middle-income countries and in the different sub-regional groupings. The results also showed that agricultural value-added reduced health expenditure in low-middleincome countries and in Latin American countries. Service value added was found to reduce health expenditure in East Asian, Pacific, and South Asia and to increase health expenditure in the Middle East and North Africa. It is therefore recommended that green production techniques and better abatement policies should be utilized in the industrial and service sectors of all economies.
Keywords: 330; Structural change; environmental pollution; Health expenditure; Driscoll-Kraay technique